An enhanced SWAT wetland module to quantify hydraulic interactions between riparian depressional wetlands, rivers and aquifers. (October 2016) - Rahman, Mohammed M.; Thompson, Julian R.; Flower, Roger J.
Abstract: This study develops a modified version of the Soil and Water Assessment Tool (SWAT) designed to better represent riparian depressional wetlands (SWATrw). It replaces existing unidirectional hydrological interactions between a wetland and a river/aquifer with a more robust bidirectional approach based on hydraulic principles. SWATrw incorporates a more flexible wetland morphometric formula and a connecting channel concept to model wetland-river interactions. SWAT and SWATrw were tested for the Barak-Kushiyara River Basin (Bangladesh and India). Although the two models showed small differences in simulated stream flow, SWATrw outperformed SWAT in reproducing river stages and the pre-monsoon river-spills into riparian wetlands. SWATrw showed that the observed presence of dry season water in the wetland was due to reduced seepage to the local groundwater table whilst continuous seepage simulated by SWAT resulted in the wetland drying out completely. The new model therefore more closely simulates the hydrological interactions between wetlands, rivers and groundwater. Highlights: A new riparian wetland module (SWATrw) is developed for SWAT. SWATrw provides improved simulation of wetland, river and aquifer interactions. SWAT and SWATrw are compared for the Barak-Kushiyara Basin (India/Bangladesh). Hydrological dynamics of the basin's wetlands are more closely simulated by SWATrw. SWATrw simulates flash floods and dry season wetland persistence. SWAT does not.